Epenthesis: The Movement of the Urdu Alveolar-Fricative Sound into the Punjabi Palatal-Affricate Sound - Pasha, A. R.; Abbas, N.; Ahmed, H. N. (Engineering, Technology & Applied Science Research, 2022)
Pakistan is a multilingual country where the Urdu language serves as lingua franca. Although Urdu is the national and official language of Pakistan, it bears the status of the second language (L2) in most of the regions due to the dominance of regional languages. The Punjabi language is the first language (L1) of the people of Punjab. This study intends to investigate the interlanguage influence and extralinguistic factors of phonological variants produced in the process of epenthesis of Punjabi palatal-affricate (/dʒ/) with the deletion of Urdu alveolar-fricative (/z/). The analysis of this study has been conducted using PRAAT software which proved that the native Punjabi speakers replace the /z/ sound with the /dʒ/ sound no matter if it occurs at the start, middle, or the end of a word. Moreover, this process of epenthesis is the result of the influence of the native language, i.e. Punjabi. The outcome of the analysis indicates that the gender and dwelling (urban or rural) of the participants have nothing to do with epenthesis. However, the education of the participants is the main reason for epenthesis.